2022
DOI: 10.3389/fgene.2022.850201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chloroplast Genomics and Phylogenetic Analysis of Thuniopsis and Closely Related Genera within Coelogyninae (Orchidaceae)

Abstract: The genus Thuniopsis was recently proposed for a rare orchid species T. cleistogama formerly classified in the genus Thunia. The relationships between Thuniopsis and its related genera have not yet been conclusively resolved. Recognition of the genus provides a new perspective to illustrate the morphological diversity and plastome evolution within Coelogyninae. In this study, we sequenced and assembled complete chloroplast (cp) genomes for three accessions of Thuniopsis cleistogama and two accessions of Thunia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
11
16
1
Order By: Relevance
“…We compared the CPGs of six species within the subgenus Gynopodium . The results indicated that the SSC and LSC regions were more divergent than IR regions, and sequences in non-coding regions were more divergent than that in coding regions, which were consistent with previous findings in Magnolia species [ 29 ] and other flowering plants [ 42 , 43 ] In this study, we identified six regions presenting significant variations in the CPGs of subgenus Gynopodium species, such as five intergenic regions: trnH - psbA , rps2 - rpoC2 , ycf4 - cemA , petA - psbJ , and ccsA - ndhD , and one gene ycf1 (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…We compared the CPGs of six species within the subgenus Gynopodium . The results indicated that the SSC and LSC regions were more divergent than IR regions, and sequences in non-coding regions were more divergent than that in coding regions, which were consistent with previous findings in Magnolia species [ 29 ] and other flowering plants [ 42 , 43 ] In this study, we identified six regions presenting significant variations in the CPGs of subgenus Gynopodium species, such as five intergenic regions: trnH - psbA , rps2 - rpoC2 , ycf4 - cemA , petA - psbJ , and ccsA - ndhD , and one gene ycf1 (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Unsurprisingly, sequence variations mainly occurred within the non-coding regions and located predominantly in the intergenic spacer regions (IGS). Similar results have been shown in other chloroplast genomes of angiosperms [17,29].…”
Section: Plastome Polymorphisms and Mutation Hotspots Of Pholidotasupporting
confidence: 90%
“…Pleione bulbocodioides and P. pleionoides (Accession Nos. NC036342 and MK810725) were included as outgroups based on previous study [17]. All the genome sequences were aligned using MAFFT v7.313 [53] and adjusted manually by BioEdit [54].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…This is consistent with the codon preference of other genera in the Orchidaceae, such as Thuniopsis and Polystachya. (Jiang et al, 2022;Li et al, 2022). Contraction and expansion of the IR region is usually observed in most angiosperms (Li et al, 2019), including Renanthera.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the codon preference of other genera in the Orchidaceae, such as Thuniopsis and Polystachya . ( Jiang et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%